Entre textos literários, não literários e vídeos: a formação do jovem leitor - Dalmédico, Daniele (2017)
The present study deals with the theme of reading: a formation of newspaper readers by the circulation between videos, literary and non-literary texts, in particular, for the production of youtubers. The aim is to identify and expand the preferences, interests and needs of literary reading of young people, once observed their approximations with autobiographical manifestations of these new communicators and different materialities of representation of their contents. This way, literary texts can be presented as challenges for the improvement of their lives. This study is justified by the fact that data concerning research are added to new reading preferences not yet measured, such as the approximation of the audiovisual and written manifestations of youtubers. For this, we consider, among others, the theoretical studies of Bakhtin (2014) that takes the dialogue as the basis of all verbal communication; Santaella (2012) on reading images; Candido (1972) and Santaella (2013) on the systematization of reader types; Benjamin (1983) on the popularization of art works; Adorno (1983) on cultural industry; Chartier (2013, 2016), Xavier (2013), Marcuschi (2005) on reading on electronic media; Jenkins (2013) on communication in the electronic media, from the perspective of media convergence; Rösing (2003, 2016) on the formation of reading mediators teachers; Jauss (1994) and Zilbermann (1989) on the theoretical principles of the Aesthetics of Reception; Eco (1991), Reis (1997) and Cerrillo (2016) on literary reading and literary reader formation. The research, of a qualitative nature, assumes characteristics of a case study, carried out through the application of a questionnaire, in a class of students of the 7th Year of Elementary Education, a corpus in which one seeks to study the contemporary youtuber phenomenon and its repercussions. It is also an action research because there is interference of the researcher in the presented reality, through the implementation of hypermidial reader practices. At the end of the study, it is evident that the formation of readers needs to cover the different languages and supports - from print to digital - in order to foster the development of a reader with different cognitive profiles. It is added to this need the urgency of valuing the school, the reading done by the students' own will and the implementation of attractive reading practices, starting with readings that constitute the horizon of students' expectations and approach them with literary artistic texts which, in addition to conferring an intellectual extension, increase the students' imagination, sensibility and critical sense.